Woodland dynamics and use during the Bronze Age: New evidence from Irish archaeological charcoal. (August 2017) - O'Donnell, Lorna
Swathes of roads and pipelines cut through the Irish landscape during the 'Celtic Tiger' years (approximately 1994–2008) leading to an unprecedented number of archaeological excavations and creating a unique opportunity for extensive research of past landscapes on a broad scale. The vast quantities of bulk soil samples suddenly available necessitated the development and adaptation of new methodologies. Despite the huge volumes of these samples, of which charcoal is the most ubiquitous ecofact, to date charcoal analysis has been considerably under-utilised in the study of past Irish woodlands. This research presents one of the largest Bronze Age archaeological charcoal datasets in Europe. It provides new palaeoecological evidence contributing to the understanding of woodland cover transformation on the island of Ireland during the late-Holocene period. The most common taxa identified in the charcoal assemblage compare well with regional pollen diagrams, particularly the use of Quercus and Corylus . With intensifying human activity during the middle Bronze Age, the proportion of Maloideae, a light demanding family rose. This is the first clear evidence of anthropogenic influence during the middle Bronze Age in Ireland derived from archaeological charcoal. The size of the charcoal dataset makes it possible to evaluate woodland cover and resourcing from two perspectives – both archaeological and palaeoecological.